Stimuli responsive drug delivery application of polymer and silica in biomedicine. Issue 44 (18th September 2015) - Gulzar, Arif; Gai, Shili; Yang, Piaoping; Li, Chunxia; Ansari, Mohd Bismillah; Lin, Jun
Abstract : In the last decade, using polymer and mesoporous silica materials as efficient drug delivery carriers has attracted great attention. Abstract : In the last decade, using polymer and mesoporous silica materials as efficient drug delivery carriers has attracted great attention. Although the development and application of them involves some inevitable barriers, such as chronic toxicities, long-term stability, understanding of the biological fate and physiochemical properties, biodistribution, effect in the biological environment, circulation properties and targeting efficacy in vivo . The construction of stimuli responsive drug carriers using biologically safe materials, followed by hydrophilic modification, bioconjugation, targeting functionalization, and detailed safety analysis in small/large animal models may be the best way to overcome these barriers. Huge progress has been made in stimuli responsive drug delivery systems based on polymer and mesoporous silica materials, mainly including pH-, thermo-, light-, enzyme-, redox-, magnetic field- and ultrasound-responsive drug delivery systems, all of which are highlighted in this review.